Some methodological problems of investment management in construction - Oleinik, Pavel P.; Schreiber, Andrey K. (Technological and Economic Development of Economy, 2004)
In recent years the processes of building design, construction and commissioning have been essentially restructured in Russia. It was achieved by introducing new energy‐efficient and resource‐saving methods and techniques reducing the time and increasing the rate of construction. However, the analysis of buildings constructed in the past few years in Russia shows that their construction time is still 1.5 ‐ 2 times longer than that of similar buildings erected in highly developed foreign countries. The investment process in construction should be considered in terms of a complex dynamic system consisting of four subsystems including the determination of major technical and economical parameters of a building (feasibility study), design, preliminary work and construction which are closely interrelated. To manage the construction process efficiently all factors influencing its major elements should be identified. To describe major factors determining the investment period they are classified into five groups. In this process more than 50 factors prolonging the investment period as a whole and at the particular stages have been identified. Summarizing the data of the comprehensive analysis of building construction allowed us to obtain major formulas for calculating all relevant investment parameters.Article in Russian.Методология управления инвестиционным процессом создания объектовStatybos investicinio proceso valdymo metodologijaSantrauka. Pastaraisiais metais Rusijoje imtasi radikalių priemonių reformuojant projektavimo, statybos ir atidavimo eksploatuoti procesus. Čia stengiamasi taikyti naujausius mokslo ir technikos laimėjimusi, taupyti išteklius, išnaudoti statybos spartinimo galimybes. Pastatų ir statinių statybos tyrimai Rusijoje atskleidė, kad jų statybos trukmė nuo 1,5 iki 2,5 karto viršija užsienio šalyse statomų analogiškų objektų statybos trukmę. Statybos investicinis projektas turi būti laikomas sudėtinga dinaminė sistema, sudaryta iš šių keturių pagrindinių etapų: techninio ir ekonominio pagrindimo, projektavimo, pasiruošimo statybai ir statybos. Šie etapai yra vienas su kitu susiję. Norint efektyviai valdyti investicinį projektą reikia nustatyti visus jį veikiančius veiksnius. Šie veiksniai suklasifikuoti pagal penkis požymius. Iš viso nustatyta daugiau kaip penkiasdešimt veiksnių, kurie daro įtaką investicinio proceso trukmei. Kiekvieno investicinio proceso etapo analize leidžia nustatyti formules, pagal kurias galima apskaičiuoti įvairius investicinius rodiklius.First Published Online: 21 Oct 2010